Problematika Perempuan dalam Novel Out Karya Natsuo Kirino (NAWA: Journal of Japanese Studies, 2024)
This research discusses various issues experienced by four female characters, Masako, Yayoi, Kuniko, and Yoshie, in the novel Out by the Japanese novelist Natsuo Kirino. Furthermore, the positive and negative impacts on those characters resulting from these issues are also analyzed. The analysis method employed is feminist literary criticism. This research uses the descriptive analytical method, which involves collecting data and utilizing various techniques to achieve the research objectives. The findings indicate that female characters experiencing oppression in the novel Out can attain freedom by understanding the oppression they face, recognizing their abilities, adapting to society, and potentially working in the public sphere. Economic factors dominate the problems they face. Apart from that, there is also domestic violence and betrayal committed by husbands. Ultimately, they worked together to eliminate Kenji, Yayoi's husband. All of these problems have positive and negative impacts. With Kenji's death, Yayoi feels free, while Masako, Kuniko, and Yoshie feel happy with the money they got from Yayoi